INOVASI MIS D'LIMA (TANYA SATU DAPAT LIMA) DI KANTOR URUSAN AGAMA (KUA) KECAMATAN TUALANG, KABUPATEN SIAK - Rahma, Mahmu Datu; Habibie, Dedi Kusuma (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze the adoption process of the Mis D'Lima (Ask for One Get Five) innovation program at the Religious Affairs Office of Tualang District Siak Regency. This program is a form of collaboration between the KUA and the UPTD of the Population and Civil Registration office of Tualang District, which provides five population administration documents after marriage through only one application, namely the marriage book, digital marriage card, marriage guidance certificate, new status KTP, and new Family Card (KK). This research uses qualitative methods with data collection techniques through interviews, observation, and documentation. The results of the study show that the Mis D'Lima (Ask for One Get Five) innovation adoption process follows five stages according to Rogers innovation diffusion theory, namely knowledge, persuasion, decision, implementation, and confirmation. The community responds positively to this program because of its convenience and efficiency, although the level of participation is still relatively low. The main obstacles in the implementation of the program are not optimal socialization to the community and the reliance on manual coordination between institutions, which has an impact on the limited reach and speed of service. Therefore, efforts are needed to increase socialization, strengthen digital coordination, and improve the service system so that this program can be implemented more widely and sustainably.